Enhancing Wear Resistance of Low Alloy Steel Applicable on Excavator Bucket Teeth Via Hardfacing - Singla, Shivali; Kang, Amardeep Singh; Grewal, Jasmaninder Singh (Asian Review of Mechanical Engineering, 2012)
New developments in the field of continuously operating earth moving equipment demand a new way of improving wear resistances of these equipment parts which directly involved with different types of sand and rocks during their operation in harsh field environment. Wear caused by the impact and abrasion action of hard particles is a major problem in the area of earth moving machinery. The objective of this study was to enhance the useful life of the excavator bucket teeth in order to decrease the idle time required to reinstate the teeth periodically during working. The objective was carried out by means of hardfacings, where the effect of the hardfacings on the extent of wear and the wear characteristics of the excavator bucket teeth were examined. Four types of ironbased hardfacing electrodes with a wide range of C (0.75-5% by weight) and Cr (2-33% by weight) were selected to deposit by manual metal arc welding process on the low alloy steel. It was observed that the wear rates of the hardfaced low alloy steel were significantly lower than those of the un-hardfaced steel, indicating a great improvement in the wear protection provided by hardfacings.